2016
DOI: 10.1161/hypertensionaha.116.08145
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Alcohol Consumption Is Associated With Left Ventricular Diastolic Dysfunction in Nonalcoholic Hypertensive Patients

Abstract: D iastolic heart failure is a frequent complication of hypertension 1 and is preceded by changes in left ventricular (LV) filling characteristics that reflect decreased compliance of the ventricular wall. In hypertension, changes in LV diastolic function occur even in the absence of ventricular hypertrophy and are associated with increased morbidity and mortality. 2 Therefore, early identification of hypertension-related LV filling changes is important to forestall subsequent cardiac deterioration leading to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Previous studies have suggested possible mechanistic links between hepatic and extrahepatic disease outcomes, as supported by findings indicating that GGT enzyme is able to fuel LDL oxidation in coronary plaques [37]. In accordance with this view, alcohol and its reactive metabolites are known to exert toxic effects virtually in all tissues and even relatively low levels of chronic drinking may increase the risk for carcinogenesis [3840], cognitive decline [41, 42], cardiac dysfunction [4345] and all-cause mortality [28, 46], which may also associate with abnormalities in blood lipid profiles and indices of inflammation [4749]. Based on the present data abnormalities in serum CRP, a widely used clinical biomarker of inflammation, and lipid profiles appear to follow the burden of unfavourable risk factors and abnormalities in markers of liver function in a sensitive manner.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have suggested possible mechanistic links between hepatic and extrahepatic disease outcomes, as supported by findings indicating that GGT enzyme is able to fuel LDL oxidation in coronary plaques [37]. In accordance with this view, alcohol and its reactive metabolites are known to exert toxic effects virtually in all tissues and even relatively low levels of chronic drinking may increase the risk for carcinogenesis [3840], cognitive decline [41, 42], cardiac dysfunction [4345] and all-cause mortality [28, 46], which may also associate with abnormalities in blood lipid profiles and indices of inflammation [4749]. Based on the present data abnormalities in serum CRP, a widely used clinical biomarker of inflammation, and lipid profiles appear to follow the burden of unfavourable risk factors and abnormalities in markers of liver function in a sensitive manner.…”
Section: Discussionmentioning
confidence: 84%
“…On the other hand, the null association between alcohol and LAVI, a measure of diastolic function, implicates a less important role of alcohol consumption in the pathophysiology of HFpEF, the other subtype of HF that is often characterized by diastolic dysfunction. Nevertheless, prospective studies using Tissue Doppler Imaging measures for diastolic function are still needed to confirm this implication, as two previous cross-sectional studies suggested a harmful association between moderate and heavy alcohol consumption and diastolic function measured with Tissue Doppler Imaging [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The present data supports the view that biochemical responses in the sequence of events leading to health problems may be expected to occur even in association with light to moderate drinking levels especially in those with precipitating risk factors. Recent findings by other groups of investigators have also emphasized the view that light to moderate drinking could be associated with an elevated risk of cancer [ 6 8 ], atrial fibrillation [ 37 ], left ventricular diastolic dysfunction [ 38 ], adverse brain outcomes [ 9 ] and an increase in all-cause mortality [ 39 ]. Although reductions in alcohol-attributable disease burden may obviously be expected to be achieved through a more efficient identification of high-risk individuals, alcohol-consuming patients seem rarely receive specific intervention in current clinical practice unless the situation is complicated by comorbidity.…”
Section: Discussionmentioning
confidence: 99%